Contemporary Version of the Monogenetic Model of Anthropogenesis—Some Critical Remarks from the Thomistic Perspective - Mariusz Tabaczek (Religions, 2023)
This article refers to the debate between proponents of mono- and polygenism. After clearly defining these two positions in reference to the distinction between mono- and polyphyletism, it presents the scientific consensus in favor of polygenism as the default model of speciation. Taking this into account, the remaining part of the article concentrates on the monogenetic model of human speciation. Approaching this topic from the Aristotelian–Thomistic perspective, it delineates the three main theological arguments and one more scientifically grounded contention in favor of monogenism and offers a critical evaluation of Kenneth Kemp’s contemporary model of theological monogenism grounded in biological polygenism. While viable, consistent, and remaining in line with the most recent paleoanthropology and human genetics, it needs to be cleared of its voluntaristic and dualistic undertones and reformulated in a way that avoids its implicit assumption of a metaphysically dubious substantial change taking place at the last step of the origin of Homo sapiens.